MAPPING OF LANDSLIDE-PRONE AREAS BASED ON REMOTE SENSING WITH GEOGRAPHIC INFORMATION SYSTEMS IN TANAH DATAR REGENCY, WEST SUMATRA - Nadyya 'Azima Muarif; Febriandi Febriandi (Remote Sensing Technology Study Program, 2022)
The aims of this study were 1) to determine the classification of landslide-prone levels in Tanah Datar Regency, 2) to and find out the causal factors for Tanah Datar Regency to be categorized as landslide-prone areas. The research method used in this study is the overlay method in the form of a combination of the results of 5 classifications (slope, rainfall, land use, geological structure, and, soil type). The type of research used is quantitative research in the form of surveys and questionnaires, statistical data sets, interviews, and, observations. The results of this study are 1) the area of Tanah Datar Regency is divided into 4 classifications of landslide-prone levels, namely low, medium, high, and very high. The landslide-prone level at the low classification level is in Pariangan District, Ten Koto District, Salimpaung District, and Sungayang District. The medium-level classification is in Batipuh District, Lima Kaum District, and Tanjung Emas District. High-level classification is in the South Batipuh District, Rembatan District, Tanjung Emas District, Padang Ganting District, Lintau Buo District, and North Lintau Buo District. Very high-level classification is in Betipuh Selatan District, Rbatan District, Tanjung Emas District, Padang Ganting District, and Lintau Buo District. Of the 14 districts dominated areas are prone to moderate landslides. This is due to the condition of the vegetation which is still very good at overcoming landslides on slopes; 2) the area of Tanah Datar Regency is included in the area prone to landslides characterized by the causal factors, namely the area with hills, excessive natural exploitation The medium level classification is in Batipuh District, Lima Kaum District, and Tanjung Emas District. High-level classification is in the South Batipuh District, Rembatan District, Tanjung Emas District, Padang Ganting District, Lintau Buo District, and North Lintau Buo District. Very high-level classification is in Betipuh Selatan District, Rbatan District, Tanjung Emas District, Padang Ganting District, and Lintau Buo District. Of the 14 districts dominated areas are prone to moderate landslides. This is due to the condition of the vegetation which is still very good at overcoming landslides on slopes; This is due to the condition of the vegetation which is still very good at overcoming landslides on slopes; 2) the area of Tanah Datar Regency is included in the area prone to landslides characterized by the causal factors, namely the area with hills, excessive natural exploitation Very high-level classification is in Betipuh Selatan District, Rbatan District, Tanjung Emas District, Padang Ganting District, and Lintau Buo District. Of the 14 districts dominated areas are prone to moderate landslides. This is due to the condition of the vegetation which is still very good at overcoming landslides on slopes; 2) the area of Tanah Datar Regency is included in the area prone to landslides characterized by the causal factors, namely the area with hills, excessive natural exploitation characterized by illegal mining, excessive extraction of wood from nature aimed at preventing landslides around slopes, infrastructure development that is not by geographical conditions, and conversion of land functions from forest areas to agricultural areas.